Improved charge injection of edge aligned MoS2/MoO2 hybrid nanosheets for highly robust and efficient electrocatalysis of H2 production. Issue 8 (17th February 2020) - Li, Shuaishuai; Zhao, Li; Lei, Shulai; Liu, Aiping; Chen, Jun; Li, Chaorong; Wu, Huaping; Lin, Liangxu
Abstract : By attaching metallic MoO2 to MoS2 to form hybrid nanosheets vertically aligned on the carbon cloth, this research demonstrates a charge injection strategy to efficiently improve the electro-catalytic performance for hydrogen production. Abstract : Molybdenum disulfide (MoS2 ) can be an efficient electro-catalyst for the hydrogen evolution reaction (HER) as an alternative to precious metals, but significant efforts are still needed to further improve its efficiency. Among various approaches, the formation of edge aligned MoS2 on an electrically conductive support is highly promising for cost-effective H2 production. Nevertheless, catalysis is highly impeded by the poor charge transport between the electrode materials and also between the multilayers of MoS2 . This research presents a strategy to improve the HER catalysis by binding layers of metallic molybdenum dioxide (MoO2 ) and MoS2 to form hybrid MoS2 /MoO2 nanosheets (attached and cross-linked to each other). Taking advantage of the hybrid structure and the mechanical strength of the carbon cloth, a catalyst with outstanding catalytic performance in the HER is demonstrated. This work shows not only a strategy to efficiently improve the electrochemical process, but also the preparation of a highly efficient catalyst for constant and robust H2 production.